A HOTS-Oriented Module: A Valid Biology Teaching Material Innovation for Grade 10 in 21st-Century Learning - Armin Arif; Yusminah Hala; Adnan (Universitas Islam Negeri Walisongo Semarang, 2026)
A Higher Order Thinking Skills (HOTS)-oriented module is a teaching material designed to develop higher-order thinking skills beyond the mastery of factual knowledge. This study employed a Research and Development approach aimed at developing a valid HOTS-oriented biology module for Grade 10 senior high school students in the even semester. The development process followed the ADDIE model, consisting of Analyze, Design, Development, Implementation, and Evaluation stages. Module validity was evaluated using expert validation sheets covering content feasibility, presentation, graphical components, and language aspects. Data were analyzed using mean scores based on predetermined validity criteria. The results showed high validity scores, with mean values of 4.64 for content, 4.57 for presentation, 4.46 for graphics, and 4.25 for language. The overall validity score was 4.48, categorized as valid. Therefore, the HOTS-oriented biology module is recommended for use in educational settings as an alternative teaching material to support learning that fosters students’ higher-order thinking skills.